EVOLUTION OF PEDAGOGY IN XX CENTURY-SADRIDDIN AINI’S REFORM OF EDUCATIONAL PRACTICES - Jumaniyazova Makhira Rahimbergan qizi, (EPRA International Journal of Research and Development (IJRD), 2023)
This article delves into the historical context of Jadidism, an independent movement that emerged after the 1905 revolution, seeking to lead the national movement in Central Asia. However, its failure to resonate with the working class led to a distinct trajectory. Focusing on the Jadidism, the article explores its influence on educational reform, particularly through the establishment of new method schools in Samarkand, Tashkent, and Bukhara. The paper then shifts to Sadriddin Aini, a prominent figure in the democratic direction, who vehemently criticized the traditional pedagogical methods prevalent in Bukhara madrasahs. Aini’s insightful critique addresses issues such as the language barrier, age-appropriate content, and the disconnect between education and students’ lives. The article concludes by highlighting Aini’s role not only as a theorist but as a dedicated educator who championed a comprehensive approach to teacher training, emphasizing cultural, scientific, and pedagogical knowledge.